Serum calcium level is related to both intima-media thickness and carotid atherosclerosis: a neglect risk factor in obese/overweight subjects - Montalcini Tiziana; Gorgone Gaetano; Pujia Arturo (Journal of Translational Medicine, 2012)
Abstract Background Experimental studies suggested that high serum calcium may be important in the pathogenesis of vascular diseases. Since calcium seems to affect specifically the cerebrovascular district, aim of this study was to determine the relation between serum calcium levels, within normal range, and subclinical atherosclerosis in the carotid arteries, in a population of obese/overweight subjects. Methods In our retrospective study we included 472 subjects (59% female) with body mass index equal to or more than 25 kg/m2. They underwent a physical examination, a biochemical assessment (including calcium evaluation) and a B-mode ultrasonography of the extracranial carotid arteries to detect carotid atherosclerosis presence and to measure intima-media thickness. Results Mean age of the population was 50 ±12 years. Prevalence of the Carotid atherosclerosis was 40%. Mean carotid intima-media thickness was 0,66 ± 0,18 mm. The univariate and multivariate analysis showed an association between calcium and carotid intima-media thickness (p = 0,035). We divided the population in serum calcium tertiles. We found an higher carotid atherosclerosis prevalence in the III tertile in comparison to that of the I tertile (p = 0,039). Conclusions In this study we found a positive relation between serum calcium levels, within normal range, and subclinical atherosclerosis in the carotid arteries, in a population of obese/overweight subjects. It is important to consider the impact of the serum calcium levels in the overall risk assessment of patients, at least in obese subjects.